Synthesis, Characterization, Antibacterial and Antifungal Activities Studies of Copper(II), Cobalt(II) and Zinc(II) Complexes of the Schiff Base Ligand Derived from 4,4-Diaminodiphenylether - Sahal, Hakan; Canpolat, Erdal; Kaya, Mehmet; Gur, Seher (Chem Soc Pakistan, 2014)
The complexes of Co(II), Cu(II) and Zn(II) with the Schiff base ligand derived from 4,4-diaminodiphenylether were prepared and characterized by physical, spectral and analytical data. The metal: ligand stoichiometric ratio is 1:1 in the complexes of Co(II) and Zn(II) whereas the metal: ligand stoichiometric ratio in the Cu(II) complex is 2:1. It was determined that the bidentate behaviors of the ligand are accomplished via the phenolic oxygen and the azomethine nitrogen atoms. The presence of water is revealed by thermograms and supported by the presence of relevant bands in their IR spectra. Suitable structures have been proposed for these complexes. The synthesized compounds were tested for antimicrobial activity against in vitro antibacterial (Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Salmonella typhimurium) and antifungal activities (Candida globrata and Candida tropicalis) by the minimum inhibitory concentration (MIC) method. All of the selected compounds showed weak antimicrobial activity against test microorganisms (128-512 mu g/mL).
Keywords: Schiff base; transition metal complexes; antimicrobial activity; 4,4-diaminodiphenylether